2018
DOI: 10.4049/jimmunol.1701578
|View full text |Cite
|
Sign up to set email alerts
|

CD22 Promotes B-1b Cell Responses to T Cell–Independent Type 2 Antigens

Abstract: CD22 (Siglec-2) is a critical regulator of B cell activation and survival. CD22 mice generate significantly impaired Ab responses to T cell-independent type 2 (TI-2) Ags, including haptenated Ficoll and pneumococcal polysaccharides, Ags that elicit poor T cell help and activate BCR signaling via multivalent epitope crosslinking. This has been proposed to be due to impaired marginal zone (MZ) B cell development/maintenance in CD22 mice. However, mice expressing a mutant form of CD22 unable to bind sialic acid l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…The role of CD22 in immune responses previously has been studied with different classes of model antigens. Although thymus-independent antibody responses of CD22-deficient mice to antigens, such as NP-ficoll, are impaired due to missing or non-functional B cell subpopulations, such as marginal zone (MZ) or B-1b B cells [17,18], thymus-dependent antibody responses to protein antigens are largely normal [9][10][11][12]. The loss of such a negative regulator would be anticipated to lead to stronger B cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CD22 in immune responses previously has been studied with different classes of model antigens. Although thymus-independent antibody responses of CD22-deficient mice to antigens, such as NP-ficoll, are impaired due to missing or non-functional B cell subpopulations, such as marginal zone (MZ) or B-1b B cells [17,18], thymus-dependent antibody responses to protein antigens are largely normal [9][10][11][12]. The loss of such a negative regulator would be anticipated to lead to stronger B cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that they are more sensitive to dysregulated signaling in the absence of CD22 ( 34 ); but it is also noteworthy that MZ precursors express the highest levels of CD22 of any B cell subset ( 35 ), implying that CD22 may be more or less required during stages in B cell development. Mice expressing all of CD22 except the extracellular domains 1 and 2 (CD22Δ1-2 mice) have reduced MZ B cells but normal TI-2 Ab responses ( 15 , 36 , 37 ), so a MZ B cell deficiency alone is not sufficient to lead to impaired TI-2 Ab responses. Recently, Haas et al ( 36 ) reported that B-1b cells from CD22 −/− mice have impaired proliferative responses and elevated Ca 2+ responses to anti-IgM ligation and that CD22 −/− mice have reduced expansion of splenic B-1b B cells after immunization with TNP-Ficoll.…”
Section: Role Of Cd22 In Response To Antigens and Pathogenic Productsmentioning
confidence: 99%
“…Mice expressing all of CD22 except the extracellular domains 1 and 2 (CD22Δ1-2 mice) have reduced MZ B cells but normal TI-2 Ab responses ( 15 , 36 , 37 ), so a MZ B cell deficiency alone is not sufficient to lead to impaired TI-2 Ab responses. Recently, Haas et al ( 36 ) reported that B-1b cells from CD22 −/− mice have impaired proliferative responses and elevated Ca 2+ responses to anti-IgM ligation and that CD22 −/− mice have reduced expansion of splenic B-1b B cells after immunization with TNP-Ficoll. There results suggest that whether or not CD22 −/− mice have defective TI-2 Ab responses depends on the Ag complexity and route of administration used.…”
Section: Role Of Cd22 In Response To Antigens and Pathogenic Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, B1 B cells can stimulate T cell expansion via CD80/CD86 and promote differentiation of CD4+ T cells (3). Similar to MZ B2 B cells, B1 B cells are capable of eliciting a T cell-independent response (40). B1 B cells differ from B2 B cells, in that they are larger, have resistance to FAS-induced apoptosis, and possess greater ex vivo survivability (41).…”
Section: B Cells Subtypes and Functionsmentioning
confidence: 99%